Analysis of providing complementary feeding practice to stunted and non-stunted children aged 6-24 months in Natuna Regency, Indonesia: A qualitative study - Nabiella, AD; Afifah, Effatul; Nurlita, Safira; Hidayanti, Misna; Mumtaz, Hammada Hanifia; Aji, Arif Sabta (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2025)
ABSTRACTBackground: Stunting was a growth disorder that occurred as a result of chronic malnutrition and repeated infections. Its prevalence had increased due to suboptimal complementary feeding (CF) practices.Objectives: The objective of this study was to describe the attitudes and confidence of mothers in the practice of providing CF among children aged 6–24 months.Materials and Methods: A descriptive qualitative study with a phenomenological approach was conducted through semi-structured interviews at Serasan and Serasan Timur Health Centers, Natuna Regency, from September to November 2024. The study explored maternal attitudes and self-confidence in complementary feeding (CF) practices. Participants included 18 primary informants in focus group discussions (9 mothers of stunted and 9 of non-stunted children) and 4 key informants in in-depth interviews (2 heads of community health centers and 2 nutritionists). Data were analyzed thematically using NVivo 12.0 software.Results: This study identified four main themes. First, maternal attitudes in facing challenges, such as food rejection and the selection of appropriate food types. Second, maternal attitudes in the practice of providing complementary feeding (CF). Third, maternal confidence in determining suitable food textures. Fourth, maternal confidence in managing picky eating during CF practices. Most mothers demonstrated a positive attitude toward CF, including preparing food themselves, considering it healthier and more economical. However, some mothers of stunted children tended to purchase instant foods more often due to practicality. The majority showed high confidence, supported by Posyandu education, internet resources, and nutritionists. Nevertheless, several mothers of stunted children still lacked confidence due to limited information on CF nutritional adequacy.Conclusion: Mothers of stunted children tended to have lower attitudes and self-confidence compared to those of non-stunted children in complementary feeding (CF) practices. Continuous education and supportive policies facilitating access to nutritious foods were essential. Additionally, family support enhanced maternal confidence in providing CF.Keywords: Attitude; children; complementary feeding; self confidence; stunting